AMELOBLASTOMA: A 5 YEAR RETROSPECTIVE ANALYSIS OF CASES IN A TERTIARY HEALTHCARE CENTER IN KERALA - Khatri R; KD Divya; Jiwane AY; Gulati S;, Balan A; R K Nileena AND P S Haris
Aim: To supplement the current database of Ameloblastoma by reporting the clinicopathologic features of Ameloblastoma cases from Kozhikode, Kerala, India. Materials and Methods: Archive records of all histologically diagnosed cases of Ameloblastoma from January 2010 through December 2014 in Department of Oral Medicine and Radiology, Government Dental College, Kozhikode, Kerala, India were analyzed with regards to age, gender, clinical manifestation, radiographic aspect, anatomical distribution and histological subtype. Results: Out of the 54 reviewed cases 31 (57.4%) were males and 23 (42.6%) were females. Mostly affected age group was second, third and fourth decades. The patient’s age varied from 12 to 65 years, with an average of 37.33 years of age at the time of diagnosis. Posterior mandible was the site of preponderance. The main histological variant seen was solid Ameloblastoma amongst which follicular were most common and none of the case of basal cell type and peripheral variant were seen. Unicystic and desmoplastic variant also found in considerable number. Conclusion: Ameloblastoma mostly affects peoples in the second to fourth decades of life, with slight male preponderance. Posterior mandible is the site of predilection. Commonly appears as multilocular radiolucent lesions but the rare variant i.e. desmoplastic appears as mixed radiopaque-radiolucent lesions. Histopathologically solid variant seen more compare to unicystic variant and desmoplastic variant. Amongst solid type follicular was most prevalent subtype. Relatively higher frequency seen in cases those were in their second decade of life.